Death Khairat Fund as The Halal Financial Management Ecosystem at Raja Haji Fi Sabilillah Mosque Malaysia An Analysis From Hifz Al-Din - Setiyawan Gunardi; Zawin Hannan Sofea Shahbuddin; Azman Ab. Rahman; Khairunneezam Mohd Noor; Ahmad Zaki Salleh; Syed Mohd Najib Syed Omar (Seybold Publications, 2024)
Non-Indexed Publication